THE ROLE OF EXTRAMURAL ENGLISH ACTIVITIES AMONG INDONESIAN SECONDARY SCHOOL STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Mahendra, Kadek Aditya; Santosa, Made Hery (Universitas Pendidikan Ganesha, 2024)
Students in EFL countries like Indonesia are nowadays expected to have good English proficiency. Even though traditional classroom activities play an important role, it cannot be denied that learning activities outside the classroom also play a significant role. These activities, known as extramural English (EE) learning, can provide additional opportunities for language practice and exposure. This study used Systematic Literature Review (SLR) in order to examine the influence of EE towards EFL secondary school students. The PRISMA method was used to filter the articles to be reviewed, and from this, around 16 studies were selected that matched the inclusions and criteria. The results show that EE does indeed increase students' overall English language skills. Moreover, the implementation of EE can also increase students’ motivation level due to its fun, engaging, and supportive environment, which will later improve the learning outcomes obtained by students.